Effect of Vermicompost and Compound inorganic Fertilizer on Soil Phosphate Availability and Yield of Potatoes (Solanum tuberosum L.) Grown in Andisols - Reginawanti Hindersah; Agnia Nabila; Ani Yuniarti (Faculty of Agriculture, Pattimura University, 2019)
Potatoes (Solanum tuberosum L.) which are comonly grown in the highland with Andisols require organic and inorganic fertilizers to maintain soil health and increase yield. The purpose of field experiment was to obtain information on the effect of vermicompost with and without NPK fertilizer on soil acidity, soil phosphor (P) availability and P uptake in potatoes shoot; as well as yield and quality of tuber. The experimental design was a randomized block design with eight treatments and three replication. The treatment consisted of a combination of vermicompost doses (5 and 10 t/ha) with NPK fertilizer doses (0; 0.5 t/ha and 1 t/ha). The two control treatments were 1) without fertilizer and 2) the method of fertilizing local farmers included 10 t /ha chicken manure and 1 t/ha NPK fertilizer. This experiment verified that vermicompost and NPK fertilizer increased plant height as well as soil P availability and acidity compared to those of control. Vermicompost has not yet substitute chicken manure to obtain the same tuber production although the percentage of marketable tuber was quite similar. Keywords : Andisols, NPK Fertilizer, Phosphorus, Potato, Vermicompost.